EFEKTIVITAS REALOKASI DANA DESA ADAT DALAM PENANGGULANGAN COVID-19 DI DESA ADAT PEMINGE, BENOA, KUTA SELATAN (CITIZEN CHARTER, 2022)
The Covid-19 pandemic, which began on 2020, had an impact on the planning and implementation of the Bali Province's Regional Budget. The Bali Regional Government released a Covid-19 response budget based on traditional village by reallocating the Traditional Village Fund with a cost cap of Rp. 300,000,000.00 (Three Hundred Million Rupiah) for each traditional village in Bali. The Traditional Village Fund reallocation effectiveness in discussing the impact of Covid-19 in Peminge Traditional Village, Bali is studied in this research. The process of identifying effectiveness uses qualitative research methodologies. This research resulted that the Traditional Village Fund Reallocation in Covid-19 pandemic treatment was effectively done, but there is still a need for improvement and optimization. There was some challenge in engaging the effectiveness indicators such as the restrictions on activities according to applicable technical guidelines, the process of disbursing funds within a quarterly period, and so on. Keywords : Effectiveness, Covid-19, and Traditional Village Fund